Unifikacja opłat stemplowych w okresie rządów sanacji — ustawa z dnia 1 lipca 1926 roku o opłatach stemplowych - Antonów, Dobrosława (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The law on stamp duties of 1 July 1926 is an important law of the interwar period in Poland. It was passed in the period of Piłsudski and his adherents’ rule. This law constituted the act of unification of stamp duties after regaining independence by Poland. It replaced more than several dozen other legal instruments, on the basis of which different public duties, recognized as stamp duties, were charged. The law was systematic in character, it included many public duties connected with economic turnover and activity of the state authorities, as well as material and procedural regulation. This law played an important role in the development of Polish finance when it was in effect and it also influenced the historical evolution of current public duties, stamp duty and tax of civil law activities among others.
Keywords: okres międzywojenny; rządy sanacji; opłaty stemplowe; naliczanie podatku